In vitro evaluation of bond strength and antibacterial activity of newly developed orthodontic self-adhesive resins (a pilot study) - Dana R. Mohammed; Ali I. Ibrahim (Journal of Orthodontic Science, 2025)
OBJECTIVES: This range-finding study aimed to develop novel primer-less self-adhesive resins (SARs) for orthodontic bracket bonding that can provide clinically acceptable bond strengths and antibacterial effects and leave minimal remnant adhesive post-bracket debonding. MATERIALS AND METHODS: Different concentrations of bioactive glass (BAG), strontium fluoride (SrF2), and powdered grape seed extract (GSE) were added to a plain SAR to develop ten adhesive formulations for brackets bonding to extracted premolars, which were subjected to thermocycling (5000 cycles) prior to shear bond strength (SBS) and adhesive remnant index (ARI) assessments. Antibacterial activity and biofilm formation tests were conducted to evaluate the antibacterial properties of the developed SARs. RESULTS: The addition of 0.5% GSE to plain SAR + BAG 1% yielded the highest SBS value with minimal ARI, yet the differences were statistically insignificant (P > 0.05). The best antibacterial performance was demonstrated by the addition of 0.5% GSE, followed by 0.5% SrF2 to the plain SAR + BAG group. CONCLUSION: Incorporating 1% BAG, combinations of 0.5% SrF2 + 3% BAG and 0.5% GSE + 1% BAG into a plain SAR yielded three newly developed formulations that provided clinically acceptable SBS with minimal adhesive remnants left on enamel post bracket debonding and improved antibacterial properties.